The acceptance of e-books usage among primary school teachers in Terengganu / Nurulsyaidatul Akma Ali - Ali, Nurulsyaidatul Akma (2014)
In this Digital Age, information technology is becoming more widespread in this country serving various sophisticated systems and gadgets that are introduced and utilized to simplify daily works. The rapid changes are also undergoing in the field of education. In Malaysia, the state of Terengganu has fore fronted the importance of technology integration in education. Thus, e book has been adopted in the education system. This research aimed to investigate the level of acceptance of e-book usage among primary school teachers in Terengganu. There were four research objectives examined which were to: i) identify the level of e-books competencies among primary school teachers in Terengganu; ii) examine the level of acceptance of e-books usage in classroom among primary school teachers in Terengganu; iii) identify the problems that arose in using ebooks in classroom and (iv) identify ways to address the problems in using e-books in classroom. 90 primary school teachers in Hulu Terengganu district in Terengganu were involved. Quantitative approach were employed with questionnaires were used as the instrument. Findings revealed that primary school teachers in Terengganu were not sure of their e-books competencies' level. However, they have positive attitude in showing their acceptance in e-books usage in classroom. As for the problems that arose in using ebooks, the primary school teachers had highlighted that one of the problems is student misused e-books provided to them. Hence, they have suggested some ways to address the problems. One of the ways is by having regular monitoring and supervision from the state government on the e-books usage in school.